Role of teriparatide in treatment of glucocorticoid-induced osteoporosis - Arthur N Lau; Jonathan D Adachi (Dove Medical Press, 2010)
Arthur N Lau, Jonathan D AdachiDivision of Rheumatology and Department of Medicine, St Joseph’s Healthcare and McMaster University, Hamilton, Ontario, CanadaAbstract: Glucocorticoids are commonly used in various fields within medicine. One of their most common and clinically significant side effects is glucocorticoid-induced osteoporosis (GIOP). GIOP is a disease leading to progressive decreases in bone mineral density, decreased bone strength, and increased risk of skeletal fractures. GIOP has a significant impact on the morbidity and health-related quality of life of the patients it affects. Glucocorticoids have deleterious effects on bone through promoting osteoblast apoptosis and inhibiting osteoblastogenesis. Teriparatide exerts anabolic effects on bone, so it is understandable why teriparatide is thought to be a rational treatment option. Clinical studies have indicated teriparatide is efficacious in the treatment of GIOP to improve bone mineral density values at the lumbar spine and femoral neck. Some evidence also suggests teriparatide may reduce rates of vertebral fractures in GIOP patients. Overall, this review of the current clinical evidence suggests teriparatide may be an efficacious and promising agent in the treatment of GIOP.Keywords: glucocorticoid-induced osteoporosis, teriparatide, parathyroid hormone